Structural and Functional Alterations of Substantia Nigra and Associations With Anxiety and Depressive Symptoms Following Traumatic Brain Injury - Gao, Liang; Xue, Qiang; Gong, Shun; Li, Gaoyi; Tong, Wusong; Fan, Mingxia; Chen, Xianzhen; Yin, Jia; Song, Yu; Chen, Songyu; Huang, Jingrong; Wang, Chengbin; et al. (Frontiers in Neurology, 2022)
Backgrounds Although there are a certain number of studies dedicated to the disturbances of the dopaminergic system induced by traumatic brain injury (TBI), the associations of abnormal dopaminergic systems with post-traumatic anxiety and depressive disorders and their underlying mechanisms have not been clarified yet. In the midbrain, dopaminergic neurons are mainly situated in the substantia nigra (SN) and the ventral tegmental area (VTA). Thus, we selected SN and VTA as regions of interest and performed a seed-based global correlation to evaluate the altered functional connectivity throughout the dopaminergic system post-TBI. Methods Thirty-three individuals with TBI and 21 healthy controls were recruited in the study. Anxiety and depressive symptoms were examined by the Hospital Anxiety and Depression Scale. All MRI data were collected using a Siemens Prisma 3.0 Tesla MRI system. The volume of SN and the global functional connectivity of the SN and VTA were analyzed. Results In the present study, patients with TBI reported more anxiety and depressive symptoms. More importantly, some structural and functional alterations, such as smaller SN and reduced functional connectivity in the left SN, were seen in individuals with TBI. Patients with TBI had smaller substantia nigra on both right and left sides, and the left substantia nigra was relatively small in contrast with the right one. Among these findings, functional connectivity between left SN and left angular gyrus was positively associated with post-traumatic anxiety symptoms and negatively associated with depressive symptoms. Conclusions The TBI causes leftward lateralization of structural and functional alterations in the substantia nigra. An impaired mesocortical functional connectivity might be implicated in post-traumatic anxiety and depression.